Orbit and origin of the LL7 chondrite Dishchii'bikoh (Arizona). (9th March 2020) - Jenniskens, Peter; Moskovitz, Nick; Garvie, Laurence A. J.; Yin, Qing‐Zhu; Howell, J. Andreas; Free, Dwayne L.; Albers, Jim; Samuels, David; Fries, Marc D.; Mane, Prajkta; Dunlap, Daniel R.; Ziegler, Karen; et al.
Abstract: The trajectory and orbit of the LL7 ordinary chondrite Dishchii'bikoh are derived from low‐light video observations of a fireball first detected at 10:56:26 UTC on June 2, 2016. Results show a relatively steep ~21° inclined orbit and a short 1.13 AU semimajor axis. Following entry in Earth's atmosphere, the meteor luminosity oscillated corresponding to a meteoroid spin rate of 2.28 ± 0.02 rotations per second. A large fragment broke off at 44 km altitude. Further down, mass was lost to dust during flares at altitudes of 34, 29, and 25 km. Surviving meteorites were detected by Doppler weather radar and several small 0.9–29 g meteorites were recovered under the radar reflection footprint. Based on cosmogenic radionuclides and ground‐based radiometric observations, the Dishchii'bikoh meteoroid was 80 ± 20 cm in diameter assuming the density was 3.5 g/cm 3 . The meteoroid's collisional history confirms that the unusual petrologic class of LL7 does not require a different parent body than three previously observed LL chondrite falls. Dishchii'bikoh was ejected 11 Ma ago from parent body material that has a 4471 ± 6 Ma U‐Pb age, the same as that of Chelyabinsk (4452 ± 21 Ma). The distribution of the four known pre‐impact LL chondrite orbits is best matched by dynamical modeling if the source of LL chondrites is in the inner asteroid belt in a low inclined orbit, with the highly inclined Dishchii'bikoh being the result of interactions with Earth before impacting.